Pendampingan Penyusunan Laporan Keuangan Pada Koperasi Perkebunan Sawit Kelompok Hudep Baru - Devi Mulia Sari; Ardian; Sri Rani Fauziah; Rizki Ramadhan; Muhammad Abthahi; Hilmi (Malik Al-Shalih : Jurnal Pengabdian Masyarakat, 2023)
Currently the New Hudep group has not prepared its financial reports properly. Therefore, the author carries out socialization regarding assistance in preparing financial reports for oil palm plantation cooperatives. The Hudep Baru group of Palm Oil Plantation Cooperatives still use simple recording of expenses and income, namely separately on another page. This is certainly not in accordance with relevant accounting standards. Apart from that, determining costs and calculating depletion are also not in accordance with PSAK. The Aceh Polytechnic Community Service Team provides assistance by providing materials and stimulating the New Hudep Group to be able to prepare their own financial reports every year.